Exploring Customer Service in Reverse Logistics Operation: A case study - Witt,Johanna (2018)
In today´s supply chains, it often ends by the consumer but as seen with reverse logistics the consumers are the starting point on the reverse flow. Reverse logistics is the opposite route from the usual supply chain and the literature stresses the importance of designing a reverse logistics network, where reverse distribution is essential to reach efficiency. The purpose of this study aims to elaborate on how service offerings within a reverse logistics operation can create customer value and value back to the operation. It will be analyzed how, and to what extent different challenges in reverse logistics can determine how value is created in such operations. Due to previous research in the field of reverse logistics has been focusing upon quantitative approaches, this study, for being able to fulfill the purpose, a qualitative approach has been used, together with a holistic single case design. The data collection consisted of using both observations and semi-structured interviews where both the case company and their customers were interviewed. The frame of reference entailed a literature review and has been summarised in a framework which the discussion has followed in a systematic approach. The discussion enlightened how service offerings can appear in a reverse logistics operation and what kind of hindrances which may appear in such environment.
Keywords: Reverse logistics; reverse distribution; B2B environment; perceived service quality